Communicating Islam is Friendly for all (CIFA) - Jandra, Mifedwil; Kilani Mohamed, Ahmad; Huda, Miftachul; Maseleno, Andino (International Journal of Psychosocial Rehabilitation, 2020)
Islam as a blessing is a religion that benefits human life and the universe. This religion must be communicated (dakwah) to mankind properly and correctly as taught by Allah in the Qur’an. The author tried to develop the concepts of communication in a framework for a missionary activity. This mindset is then examined by measuring data in the field with SEM analysis techniques. The results of the study show that Islam as a blessing will be realized when delivered with friendly dakwah, whose begins with social studies, makes proper planning and carries out careful communication in terms of methods, presentation, themes and forms of communication. The effect will produce a happy life for the people.